Building on common ground to address biodiversity conflicts and foster collaboration in environmental management. (15th August 2018) - Lecuyer, Lou; White, Rehema M.; Schmook, Birgit; Calmé, Sophie
Abstract: Conservation biology faces critical challenges that require collaborative approaches, including novel strategies to support interactions among actors in biodiversity conflicts. The goals of this study were to investigate the concept of common ground across multiple issues and to explore its practical application for the support of environmental management. We conceptually defined common ground as the areas of relevance underlying the suite of issues expressed by people regarding environmental management in a particular context. We then empirically tested this in the Calakmul region of Mexico, where the complex socio-historical context and high biodiversity have created environmental management challenges that are now being addressed by a local, multi-stakeholder management board. We conducted 26 open interviews with members of the board and a further round of quantitative prioritisation of issues raised. Using a coding process designed to reveal common ground, we categorized the issues at four levels ranging from coarse to fine ( themes, topics, sub-topics and perspectives ). We then analysed two levels, topics (n = 14 issues) and sub-topics (n = 51 issues). To do so, we built common ground matrices to identify and analyze common ground among actors and across issues. First, cluster and non-metrical data analyses revealed the diversity of actor positions and the lack of consistent grouping among actors by occupational activity. This demonstrated that focusing on actors' differences might be misleading, and that actors' views were not closely aligned with their roles. Second, we located issues according to their levels of common ground and importance among actors. We showed that by not focusing on single issue conflicts, the identification of common ground across multiple issues can pinpoint synergies. We then proposed a framework for collaboration that prioritizes issues of high importance with greater common ground (e.g. sustainable resource use activities), to support the development of trust and norms of reciprocity among actors, strengthening the potential for future cooperation. By adopting this approach, environmental managers could support the initial stages of collaborative conservation strategies, engaging with other actors to seek common ground, avoid the creation of polarised groups and help effectively manage biodiversity conflicts. Highlights: How to define, identify, and develop common ground to foster collaboration is proposed. Finding common ground on multi-issues reveals diverse perspectives within predefined groups. The pursuit of common ground uncovers potential synergies and trade-offs across issues. Considering issue's importance and common ground supports first stage of collaboration. Engaging with actors to seek common ground can help manage biodiversity conflicts.